Proyecto producción y comercialización de cafété - Gómez, J. (2010)
This work of investigation research to introduce to the market of Guayaquil a new product named "CAFETE", using a strategy that allows to determine the requirements of the consumer, this way to offer a traditional drink that fills all their expectations with a modern and innovative approach. The value added of this product is in his presentation, offering a delicious coffee passed in practices bags ready to be tasted where in addition the aroma, flavor was preserved, nutritional values and of equal form satisfy the need to have it in any place and without loss of time. We realize surveys bearing in mind the population in general of the city of Guayaquil, this wants to say without distinction of age, marital status, genre, of all the sectors of the cit y and with the principal characteristic of their ways of life are persons with a little available time due to their daily activities. We determine that the throwing of the product would have a great reception and success , on having determined that a great percentage of persons is consuming coffee passed, which is a product of massive and frequent consumption, that the supermarkets are the principal points where the potential consumers are tasty of acquiring it, and which the price that offered to the public had a great acceptance . Also it was possible to determine by means of the financial study that the product is very profitable and that the product has big possibilities of being accepted inside the market, which meets reflected in the level of projected sales and in the significant TIR that was obtained.